2018
DOI: 10.1039/c7nr07935d
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanohybrid-based SERS chips armed with an internal standard for broad-range, sensitive and reproducible simultaneous quantification of lead(ii) and mercury(ii) in real systems

Abstract: Lead ions (Pb) and mercury ions (Hg), the two commonly coexisting heavy metal ions, pose severe risks to environment and human health. To date, no surface-enhanced Raman scattering (SERS) sensor has been reported for the simultaneous quantification of Pb and Hg in real systems. Herein, the first demonstration of SERS chips for simultaneous quantification of Pb and Hg in real systems is presented based on the combination of reproducible silicon nanohybrid substrates and a corrective internal standard (IS) sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…As aresult, the produced fluorescence fingerprint spectrum could successfully indicate the presence of the detected ions ( Figure 3b). [23] In addition, the DNA-modified SERS sensor can also be used for multiplexed detection of metal ions.S hi et al [24] demonstrated aS ERS chip that is capable of simultaneous detection of Pb 2+ and Hg 2+ through functionalized Pb 2+ -a nd Hg 2+ -specific DNAs trands in real systems.B yi ntroducing an internal standard to reduce the variances from instrumental and measurement conditions, both of the heavy metal ions can be quantified with alow limit of detection, suggesting ap owerful tool for on-site detection of heavy metal ions ( Figure 3c).…”
Section: In Vitro Multiplexed Sensingmentioning
confidence: 99%
“…As aresult, the produced fluorescence fingerprint spectrum could successfully indicate the presence of the detected ions ( Figure 3b). [23] In addition, the DNA-modified SERS sensor can also be used for multiplexed detection of metal ions.S hi et al [24] demonstrated aS ERS chip that is capable of simultaneous detection of Pb 2+ and Hg 2+ through functionalized Pb 2+ -a nd Hg 2+ -specific DNAs trands in real systems.B yi ntroducing an internal standard to reduce the variances from instrumental and measurement conditions, both of the heavy metal ions can be quantified with alow limit of detection, suggesting ap owerful tool for on-site detection of heavy metal ions ( Figure 3c).…”
Section: In Vitro Multiplexed Sensingmentioning
confidence: 99%
“…For the simultaneous detection of lead (Pb 2+ ) and mercury (Hg 2+ ), Shi et al developed silicon SERS chips including an internal standard sensing strategy [ 28 ]. For the detection in industrial wastewater, a silicon wafer was coated with AgNPs as an internal standard and the NPs were modified with 4-aminothiophenol (4-ATP).…”
Section: Environmental Sensingmentioning
confidence: 99%
“…In addition, the DNA‐modified SERS sensor can also be used for multiplexed detection of metal ions. Shi et al . demonstrated a SERS chip that is capable of simultaneous detection of Pb 2+ and Hg 2+ through functionalized Pb 2+ ‐ and Hg 2+ ‐specific DNA strands in real systems.…”
Section: In Vitro Multiplexed Sensingmentioning
confidence: 99%